AL-QAWĀID AL-FIQHIYYAH TERHADAP PERBEDAAN PENDAPAT DALAM FIQIH (KASUS HUKUMAN TINDAK PIDANA KORUPSI) - Teguh Luhuringbudi; Achmad Yani (Institut Agama Islam Negeri Kendari, 2018)
This study discusses the attitude of corruption based on the perspective of al-Qawāid al-Fiqhiyyah. Corruption is a symptom of a dilemma because of its position not only as an extraordinary crime, but also as a human actualization to feel the hierarchy of needs. This requires a subjective attitude-primordialist-dogmatic in the form of Islamic views with a jurisprudential (fiqh) approach and perspective of al-Qawāid al-Fiqhiyyah in addressing the two symptoms of the dilemma. The attitude and view of al-Qawāid al-Fiqhiyyah to the punishment of corruption by methodology is done by six categories of rules (major theory) consisting of fourteen applied rules (minor theory). This paper concludes that the attitude of corruption criminal cases can be done with five things; the completion of the Highly Political Cost System, confirmation and tightening of law enforcement, alleviating the economic factors of the government apparatu, to sharpen and culture the hedonism and consumerism, and religious moral preservation.